Mitigate+ at COP 27: Let’s talk about low-emission food systems! - Villarino, Maria Eliza J. (CGIAR System Organization, 2022)
At the Food and Agriculture Pavilion at COP 27 in Sharm El Sheikh, Egypt, Mitigate+ held a session that explored the potential for integrating food system approaches into those strategies, known as LT-LECRDS for short. Per Article 4 of the Paris Agreement, "all Parties should strive to formulate and communicate long-term low greenhouse gas emission development strategies, mindful of Article 2 taking into account their common but differentiated responsibilities and respective capabilities, in the light of different national circumstances.”